THE ANALYSIS OF UNIT-SHIFTS IN A SUBTITLE OF THE HOBBIT THIRD SEQUEL - Zoraya, Rita; Sutopo, Djoko; ., Yuliati (ELT Forum: Journal of English Language Teaching, 2017)
This final project is about the analysis of unit-shifts that occur in the translation of subtitle a film entitled The Hobbit: The Battle of the Five Armies. Various subtitles were already created to make it easier for audience to understand this film. The result of this study shows that there are 14 unit-shifts that occur with various frequencies. With 144 of total unit-shifts that occur in this study, the detail of each unit-shift type as follow: 2 unit-shifts for Morpheme into Phrase type; 8 unit-shifts for Morpheme into Word type; 5 unit-shifts for Phrase into Sentence type; 9 unit-shifts for Sentence into Phrase type; 12 unit-shifts for Clause into Sentence type; 14 unit-shifts for Sentence into Clause type; 23 unit-shifts for Clause into Word type; 1 unit-shift for Word into Clause type; 35 unit-shifts for Phrase into Word type; 5 unit-shifts for Word into Phrase type; 22 unit-shifts for Sentence into Word type; 6 unit-shifts for Word into Sentence type; 1 unit-shift for Phrase into Clause type; and 1 unit-shift for Clause into Phrase type.